Die arsakidische Nebenlinie in Armenien - Schottky, Martin (Anabasis. Studia Classica et Orientalia, 2019)
Continuous Arsacid rule in Armenia began in 52 (66) AD with Tiridates I. He was the ancestor of the Armenian Arsacids, who embraced seven generations until the downfall of Parthia around 226. Not everybody of them became king. Tiridates’ great-grandson Vałarsh was neglected in favour of Roman nominees, while his presumable son Tiridates was appointed satrap at least. Only the latter’s heir Khosrov, contemporary of the first Severan emperors in Rome, became king again. He was a victim of Caracalla’s chaotic policy and disappeared in 214. His son Tiridates II achieved his recognition by Caracalla’s successor Macrinus. Several years later, the Parthian main line of the Arsacids and their empire were extinguished by the Sasanians. Tiridates took over some Parthian military units and defended his kingdom successfully against the first Persian attack under Ardashir I. He was the progenitor of the later Armenian Arsacids, who survived for additional 200 years. The Caucasian historical tradition lets rule Arsacids in Armenia since the second half of the second century BCE, whereas the great kings of kings of Parthia were more or less forgotten.